NEW MEMBERS OF DECAPOD FAUNA IN FINIKE BAY, TURKEY - Mehmet Gökoğlu; Erkan Biçer; Ferhat Çağıltay; Jale Korun; Mesut Yılmaz; Alper Yıldız (AQUASAINS, 2023)
Shrimp fishing is done by trawling in the deep waters of Antalya and Finike Gulfs. The shrimp species generally caught during this fishing are Aristaeomorpha foliacea, Aristeus antannatus, Plesionika edwardsii, P. martia.  Besides these species, Pasiphea multidentata and P. sivado, which have no economic value, are rarely caught. Two different shrimp species were caught during trawling in the 400-500 m deep waters of Finike Bay on February 7, 2022. Since the fishermen did not know the shrimp species they caught, they wanted the species to be identified. It has been determined that these shrimp species caught in the deep waters of Finike Bay are Oplophoroidae family members i.e. Acanthepyra eximia and A. pelagica. These caught shrimps are pelagic species. With the discovery of these species in the Finike Bay, two more species were added to the Decapod fauna of the Finike Bay.